Persistent Hypoglycemia: A Rare Case Report Of Clinically Diagnosed Insulinoma - Putri, Hesti Andika; Febryan, Reza (Jurnal Health Sains, 2025)
Insulinoma is a rare disease, with an incidence of approximately 4 cases per 1 million people per year. It is a pancreatic tumor that produces insulin and is classified as one of the functional pancreatic neuroendocrine tumors, originating from the pancreatic ductal cells. In insulinoma, insulin is produced abnormally and continuously, leading to persistent hypoglycemia due to excessive insulin levels. We report a case of a 49-year-old female patient who presented to the emergency department with a chief complaint of generalized weakness. The weakness was persistent and typically occurred before meals, improving after the consumption of sugar water. The patient also reported dizziness, cold sweats, blurred vision, and tremors. Laboratory tests revealed a random blood glucose level of 35 mg/dL, a fasting insulin level of 82.4 µIU/mL, and a C-peptide level of 1.07 ng/mL. Abdominal CT scan did not detect a pancreatic mass, and MRI findings were also inconclusive. Therefore, further evaluation with Endoscopic Ultrasound (EUS) and GLP-1R PET/CT was recommended. The diagnosis of insulinoma was made based on clinical and biochemical findings, fulfilling Whipple’s triad and the diagnostic criteria of blood glucose < 55 mg/dL, insulin ≥ 55 µIU/mL, and C-peptide ≥ 0.6 ng/mL. The therapeutic algorithm for clinically and biochemically confirmed insulinoma includes: stabilization of hypoglycemia, evaluation of tumor resectability, and administration of medical therapies such as everolimus, peptide receptor radionuclide therapy (PRRT) with Lu-177, chemotherapy, and local ablation techniques in cases of refractory disease.